DPYD variant testing in candidates for fluoropyrimidine treatment: A study protocol - Ana Hernández-Guío; M.ª Ángeles Bernabéu-Martínez; Andrés Corno-Caparrós; M.ª Teresa Aznar-Saliente; Manuel Bonete-Sánchez; Miguel Ángel Calleja-Hernández (Elsevier, 2021)
Objective: The main purpose of this study is to evaluate the potential clinical impact of pharmacogenetic testing on the reduction of the toxicity in patients treated with fluoropyrimidines. This will be achieved by comparing the frequency of adverse events and the incidence of toxicity of two groups of patients that will differ from each other only in that one will receive pharmacogenetic counseling. The hypothesis is that availability of a pharmacogenetic report prior to treatment initiation has a positive effect. One of the main secondary goals is to analyze allele frequencies and the association of polymorphisms rs895819 (miR27A) and rs1801160 (DPYD*6) with toxicity by conducting an observational study to determine their clinical relevance and standardize a dose adjustment recommendation. Method: The study has an single-center ambispective, quasi-experimental design and is based on a multidisciplinary protocol involving implementation and standardization of DPYD*2A; DPYD*13; c.2846A>T; and HapB3 measurements. Following these measurements, pharmacogenetic counseling will be carried out and its clinical impact will be evaluated. The primary endpoint of the study is severe toxicity and/or mortality. The toxicity observed in two groups with similar epidemiological characteristics will be compared: the intervention group (candidates for treatment with fluoropyrimidines who will be subjected to the protocol) and the control group (retrospective cohort). Additionally, rs895819 (MIR27A) and rs1801160 (DPYD*6) will be determined. Testing for these variants is not part of the hospital's daily practice, nor are they included in clinical guidelines. However, according to recently published studies, the activity of dihydropyrimidine dehydrogenase might be affected by these variants, as they may be associated with toxicity. The results of the measurements of these two variants will not be incorporated to pharmacogenetics counseling until their association with toxicity is determined by means of the observational study to be conducted. The project, as well as the patient information sheet and the informed consent form, were approved by the Ethics Committee of the participating center (code 20/006).